Consequences of Convenience, Trustworthiness and Price to Customer Perceived Value - Jamaludin, Rian Maulana; Risasono, Fadhil Dhafa; Hisyam, Jasheer Muhamad; Rahayu, Fatik (Golden Ratio of Data in Summary, 2025)
This study aims to explore the impact of convenience, trustworthiness, and price on customer perceived value in the context of online food delivery services in Indonesia. Data were collected through questionnaires distributed to users of online food delivery services using purposive sampling, with a total of 200 respondents. Data analysis was conducted using Structural Equation Modeling (SEM) to examine the relationships between these variables. The results of the study indicate that convenience and price have a significant positive effect on customer perceived value. Conversely, trustworthiness does not show a significant impact on customer perceived value. These findings suggest that the convenience of using the application and competitive pricing are key factors in enhancing customer perceived value. Therefore, online food delivery service companies are advised to continuously improve features that provide convenience and offer competitive pricing to maintain and enhance customer perceived value.